In Vivo and In Vitro Evaluation of the Feasibility and Safety Profiles of Intraarticular Transplantation of Mitochondria for Future Use as a Therapy for Osteoarthritis - Carlos Vaamonde-Garcia; Tamara Hermida-Gómez; Sara Paniagua-Barro; Elena F. Burguera; Francisco J. Blanco; Mercedes Fernández-Moreno (Cells)
Osteoarthritis (OA) is the most common rheumatologic disease and a major cause of pain and disability in older adults. No efficient treatment is currently available. Mitochondrial dysfunction in chondrocytes drives molecular dysregulation in OA pathogenesis. Recently, mitochondrial transfer to chondrocytes had been described, enabling transplant of mitochondria as a new avenue to modify the OA process, although evidence on its feasibility and safety remains limited.The primary objective of this study was to demonstrate the feasibility and safety of intra-articular mitochondrial transplantation. Mitochondria were isolated from liver using the procedure described by Preble and coworkers combined with magnetic beads coupled to anti-TOM22 antibodies. The organelles obtained were analyzed to determine their purity and viability. The safety and viability of the administration of the isolated mitochondria into articular tissues as well as the integration and distribution of the transplanted mitochondria within joint tissues were analyzed using both in vitro and in vivo models. We established an efficient, reproducible, effective, and rapid protocol for isolating mitochondria from liver. We obtained mitochondria with high viability, yield, and purity. The isolated mitochondria were injected into joint tissue using both in vitro and in vivo models. Functional mitochondria were detected in the extracellular matrix of the cartilage, menisci and synovium. Our results establish a safe and viable protocol for mitochondrial isolation and intra-articular injection. The methodology and findings presented here pave the way for future studies in osteoarthritis models to validate mitochondrial transplantation as a potentially effective treatment for OA.